Iterated Prisoners Dilemma with limited attention - Çetin, U.; Bingol, H.O. (Condensed Matter Physics, 2014)
How attention scarcity effects the outcomes of a game? We present our findings on a version of the Iterated Prisoners Dilemma (IPD) game in which players can accept or refuse to play with their partner. We study the memory size effect on determining the right partner to interact with. We investigate the conditions under which the cooperators are more likely to be advantageous than the defectors. This work demonstrates that, in order to beat defection, players do not need a full memorization of each action of all opponents. There exists a critical attention capacity threshold to beat defectors. This threshold depends not only on the ratio of the defectors in the population but also on the attention allocation strategy of the players. Як дефiцит уваги впливає на результати гри? Ми представляємо нашi результати на прикладi гри Iтерована дилема в’язня (Iterated Prisoners Dilemma (IPD)), в якiй гравцi можуть погоджуватися чи вiдмовлятися
грати зi своїм партнером. Ми вивчаємо вплив розмiру пам’ятi на визначення вiдповiдного партнера для
взаємодiї. Ми дослiджуємо умови, при яких ймовiрнiше стати партнерами нiж перебiжчиками. Ця робота
демонструє, що для перемоги над дезертирством гравцi не потребують повного запам’ятовування кожної
дiї всiх опонентiв. Для того, щоб перемогти перебiжчикiв iснує критичний порiг здатностi уваги. Цей порiг
залежить не тiльки вiд частки перебiжчикiв в популяцiї, але також вiд стратегiї розподiлу уваги гравцiв.